2015
DOI: 10.1088/0960-1317/25/12/125003
|View full text |Cite
|
Sign up to set email alerts
|

Silk and PEG as means to stiffen a parylene probe for insertion in the brain: toward a double time-scale tool for local drug delivery

Abstract: The use of soft materials as substrate for neural probes aims at achieving better compliance with the surrounding neurons while maintaining minimal rejection. Many strategies have emerged to enable such probes to penetrate the cortex, among which the use of resorbable polymers. We performed several tests involving two resorbable polymers considered most promising: polyethylene glycol (PEG) and silk fibroin (SF) from Bombyx Mori silkworms. Our coating method provides a repeatable, uniform structure optimized fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 61 publications
9
85
0
Order By: Relevance
“…However, the low stiffness of flexible neural probe makes it susceptible to bending and buckling during insertion into the brain. To deal with this dilemma, several delicate strategies have been developed to guide the insertion such as transient shuttles with dissolvable support materials such as silk, sugars, hydrogel or polyethylene glycol (PEG) as coatings, metal as rigid backbone layers for insertion, and removable shuttles with SU‐8 shanks or microneedles as temporary carriers. To remove the need of additional materials that may displace tissue in shuttle strategies, mechanically adaptive materials that change modulus on exposure to physiological conditions have been utilized as the probe substrates despite the potential biocompatibility issue.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low stiffness of flexible neural probe makes it susceptible to bending and buckling during insertion into the brain. To deal with this dilemma, several delicate strategies have been developed to guide the insertion such as transient shuttles with dissolvable support materials such as silk, sugars, hydrogel or polyethylene glycol (PEG) as coatings, metal as rigid backbone layers for insertion, and removable shuttles with SU‐8 shanks or microneedles as temporary carriers. To remove the need of additional materials that may displace tissue in shuttle strategies, mechanically adaptive materials that change modulus on exposure to physiological conditions have been utilized as the probe substrates despite the potential biocompatibility issue.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential benefit of soft implants, they are generally designed for primary use at the brain surface, or at depths up to a few millimeters. Otherwise, soft implants normally require the use of needle guide or stiff coating (such as polyethylene glycol (PEG) or biodegradable silk) for aiding tissue penetration and trajectory to deep brain tissue.…”
Section: Microfabricated Electrochemical Probesmentioning
confidence: 99%
“…[102] D) Subcellular probef or dopamine detection madebyc ombination of assembly of carbon fiber and microfabricationo fp arylene insulator. [103] able silk [138,139] )f or aiding tissue penetration and trajectoryt o deep brain tissue.…”
Section: Polymer Probesmentioning
confidence: 99%
“…A critical challenge to these and other very soft electrodes is insertion into the brain due to their fragility and lack of mechanical stiffness. Previous research has shown that compliant electrodes can be inserted using mechanical shuttles (22), stiffening agents (23,24), or syringes (14). However, standard shuttles for a planar array of the NeuroRoots would be hundreds of microns wide and cause significant damage on their own.…”
Section: Introductionmentioning
confidence: 99%